Incentive mechanism for performance-based payment of infrastructure PPP projects: coupling of reputation and ratchet effects - Li, Huimin; Su, Limin; Zuo, Jian; Zhao, Xianbo; Chang, Ruidong; Wang, Fuqiang (International Journal of Strategic Property Management, 2022)
The performance-based payment PPP model has been widely used in the infrastructure projects. However, the ratchet effect derived from performance-based reputation incentives has been largely overlooked. To overcome this shortcoming, ratchet effect is considered in the performance-based payment incentive process. A multi-period dynamic incentive mechanism is developed by coupling the reputation and ratchet effect. The main results show that: (1) Under the coupling of reputation and ratchet effects, the optimal incentive coefficient in the last performance assessment period is always greater than that of the first period. The bargaining power can replace part of the incentive effect; (2) Due to the ratchet effect, if the government improve performance targets through performance adjustment coefficients, it needs to increase incentives to overcome the decreasing effort of the private sector; (3) When the bargaining power and punishment coefficient are small, the reputation incentive is replacing the explicit incentive. The increasing incentive coefficient would make the ratchet effect dominant the reputation effect; (4) To prevent the incentive incompatibility derived from the ratchet effect, the government should increase the incentive while increasing the punishment to achieve the “penalties and rewards”. This study provides theoretical and methodological guidance to design incentive contracts for infrastructure PPP projects.First published online 06 January 2022